Production and partial characterization of two types of phytase from aspergillus niger NCIM 563 under submerged fermentation conditions - Soni, Sarvesh Kumar; Khire, Jayant Malhar (World Journal of Microbiology & Biotechnology, 2007)
Novel extracellular phytase was produced by Aspergillus niger NCIM 563 under submerged fermentation conditions at 30 degrees C in medium containing dextrin and glucose as carbon sources along with sodium nitrate as nitrogen source. Maximum phytase activity (41.47 IU/mL at pH 2.5 and 10.71 IU/mL at pH 4.0) was obtained when dextrin was used as carbon source along with glucose and sodium nitrate as nitrogen source. Nearly 13 times increase in phytase activity was observed when phosphate in the form of KH2PO4 (0.004 g/100 mL) was added in the fermentation medium. Physic-chemical properties of partially purified enzyme indicate the possibility of two distinct forms of phytases, Phy I and Phy II. Optimum pH and temperature for Phy I was 2.5 and 60 degrees C while Phy II was 4.0 and 60 degrees C, respectively. Phy I was stable in the pH range 1.5-3.5 while Phy II was stable in the wider pH range, 2.0-7.0. Molecular weight of Phy I and Phy II on Sephacryl S-200 was approximately 304 kDa and 183 kDa, respectively. Phy I activity was moderately stimulated in the presence of 1 mM Mg2+, Mn2+, Ca2+ and Fe3+ ions and inhibited by Zn2+ and Cd2+ ions while Phy II activity was moderately stimulated by Fe3+ ions and was inhibited by Hg2+, Mn2+ and Zn2+ ions at 1 mM concentration in reaction mixture. The Km for Phy I and II was 3.18 and 0.514 mM while Vmax was 331.16 and 59.47 mu mols/min/mg protein, respectively.
Keywords: Aspergillus niger; Phytase; phytate degradation; Poultry feed supplement; Submerged fermentation

Influence of pretreatment of agriculture residues on phytase production by aspergillus niger NCIM 563 under submerged fermentation conditions - Bhavsar, Kavita P.; Shah, Parin; Soni, Sarvesh Kumar; Khire, Jayant Malhar (African Journal of Biotechnology, 2008)
The extracellular phytase production by Aspergillus niger NCIM 563 was evaluated in medium containing various agriculture residues under submerged fermentation conditions. Phytase production was affected by inorganic phosphate content of agriculture residues which ranged from 2.8 to 8 mg/g. The agriculture residues containing less than 4 mg/g inorganic phosphate supported phytase production with maximum activity of 68 IU/ml in medium containing 1% rice bran on 11(th) day of fermentation. Addition of glucose up to 5% in fermentation medium containing 1% rice bran, enhanced phytase production. Pretreatment of agriculture residues with water to remove excess inorganic phosphate has significantly enhanced the phytase activity in case of de-oiled rice bran, wheat bran, peanut cake (low and high oil) and coconut cake. Maximum increase of 20.3 times in phytase activity was observed in case of wheat bran as compared to de-oiled rice bran, coconut cake, peanut cake high and low oil in which the increase in phytase activity was 6.85, 6.1, 5.3 and 3.0 times, respectively. Maximum phytase activity of 68 IU/ml was produced on the 11(th) day of fermentation compared to earlier reported 41.47 IU/ml phytase activity on the 15(th) day of submerged fermentation using 5% dextrin and 2.5% glucose, thus increasing productivity.
Keywords: Agriculture residue; Aspergillus niger; Phytase; phytate degradation; Poultry feed supplement; Submerged fermentation

Self–assembled histidine acid phosphate nanocapsules as templates for multifunctional hollow platinum nanospheres in ionic liquid [BMIM][BF 4 ] for drug delivery - Soni, Sarvesh Kumar; Sarkar, Sampa; Sarkar, Dhiman; Coloe, Peter J.; Bhargava, Suresh Kumar; Bansal, Vipul (Proceedings of Chemeca, 2012)
During the past few decades, the design and fabrication of nano drug delivery vehicle has received considerable attention for incorporating multi-functionality, emphasizing transportation of anticancer drugs to tumour sites. Protein-based nanoparticles hold significant promise in the development of anticancer drug delivery systems since they have remarkable superiority in biocompatibility, biodegradability and natural metabolism in physiologic systems. Ionic liquids (ILs) are a class of solvents that are composed solely of ions (ILs – commonly referred as room temperature molten salts or room temperature ionic liquids). They have recently emerged as green solvents or green reaction media, because of their reported unique physico-chemical properties. We report for the first time the controlled self-assembly of Histidine Acid phosphatase (HAP) enzyme in the IL 1-butyl-3-methylimidazolium tetrafluoroborate [BMIM][BF 4 ], leading to the formation of HAP nanocapsules as template for synthesis of platinum nanospheres. These HAP nano-containers were loaded with an anticancer drug curcumin. We further demonstrated in vitro drug release and synergistic anticancer effect of these systems on three different cell lines viz. hepatocellular carcinoma (HepG2), breast cancer (MCF-7) and human acute monocytes (THP-1). The present work can extend our theoretical understanding on nano-bio interfacial molecular self assembly and will facilitate the motivated insights of inorganic/organic hybrid nano-materials/ nano-particles/ nano-objects and ionic liquids based multi functional drug delivery vehicles with synergistic combination chemotherapy for potential application in tumor targeting. INTRODUCTION During the past few decades, the design and fabrication of drug delivery vehicle has received considerable attention for incorporating multi-functionality emphasizing transportation of anticancer drugs to tumour sites. These nano drug delivery vehicles have many advantages including prolonged circulation time of the drugs (Duncan, 2003, Kiick, 2007) , improved drug targeting and solubility (Duncan, 2003, Kiick, 2007), higher payloads (Duncan, 2003) and controlled release of the therapeutics into the blood stream or the targeted tumour tissues (Uhrich et al. 1999, Duncan, 2003).

Detection of a target protein (GroEl2) in Mycobacterium tuberculosis using a derivative of 1,2,4-triazolethiols - Sarkar, Sampa; Swami, Sagar; Soni, Sarvesh Kumar; Holien, Jessica K.; Khan, Arshad; Korwar, Arvind M.; Likhite, Anjali P.; Joshi, Ramesh A.; Joshi, Rohini R.; Sarkar, Dhiman (Molecular Diversity, 2022)
Herein, we identified a potent lead compound RRA2, within a series of 54 derivatives of 1,2,4-triazolethiols (exhibit good potency as an anti-mycobacterial agents) against intracellular Mycobacterium tuberculosis (Mtb). Compound RRA2 showed significant mycobactericidal activity against active stage Mycobacterium bovis BCG and Mtb with minimum inhibitory concentration (MIC) values of 2.3 and 2.0 mu g/mL, respectively. At MIC value, RRA2 compound yielded 0.82 log reduction of colony-forming unit (cfu) against non-replicating Mtb. Furthermore, RRA2 compound was selected for further target identification due to the presence of alkyne group, showing higher selectivity index (> 66.66 +/- 0.22, in non-replicating stage). Using ``click'' chemistry, we synthesized the biotin linker-RRA2 conjugate, purified with HPLC method and confirmed the conjugation of biotin linker-RRA2 complex by HR-MS analysis. Furthermore, we successfully pulled down and identified a specific target protein GroEl2, from Mtb whole-cell extract. Furthermore, computational molecular modeling indicated RRA2 could interact with GroEl2, which explains the structure-activity relationship observed in this study.
Keywords: 1; 2; 4-triazolethiols; GroEl2; Mycobactericidal activity; Mycobacterium bovis BCG; Mycobacterium tuberculosis